Characterization of α-Glucosidases From Lutzomyia longipalpis Reveals Independent Hydrolysis Systems for Plant or Blood Sugars - da Costa, Samara G.; Bates, Paul; Dillon, Rod; Genta, Fernando Ariel (Frontiers in Physiology, 2019)
Lutzomyia longipalpis is the main vector of Leishmania infantum and exploits different food sources during development. Adults have a diet rich in sugars, and females also feed on blood. The sugar diet is essential for maintaining longevity, infection and Leishmaniasis transmission. Carbohydrases, including α-glucosidases, are the main enzymes involved in the digestion of sugars. In this context, we studied the modulation of α-glucosidase activities in different feeding conditions and compartments of Lutzomyia longipalpis females, in order to characterize in detail their roles in the physiology of this insect. All tissues showed activity against MUαGlu and sucrose, with highest activities in the midgut and crop. Activity was 1000 times higher on sucrose than on MUαGlu. Basal activities were observed in non-fed insects; blood feeding induced activity in the midgut contents, and sugar feeding modulated activity in midgut tissues. α-glucosidase activity changed after female exposure to different sugar concentrations or moieties. α-glucosidases from different tissues showed different biochemical properties, with an optimum pH around 7.0 - 8.0 and KM between 0.37 - 4.7 mM, when MUαGlu was used as substrate. Using sucrose as substrate, the optimum pH was around 6.0, and KM ranges between 11 - 800 mM. Enzymes from the crop and midgut tissues showed inhibition in high substrate concentrations (sucrose), with KI ranging from 39 to 400 mM, which explains the high KM values found. Chromatographic profiles confirmed that different α-glucosidases are been produced in L. longipalpis in different physiological contexts, with the distinction of at least four α-glucosidases. The results suggest that some of these enzymes are involved in different metabolic processes, like digestion of plant sugars, digestion of blood glycoproteins or glycolipids, and mobilization of energetic storages during starvation.